2008
DOI: 10.1038/sj.bjc.6604785
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial immune modulatory effects of a specific nutritional combination in a murine model for cancer cachexia

Abstract: The majority of patients with advanced cancer are recognised by impaired immune competence influenced by several factors, including the type and stage of the tumour and the presence of cachexia. Recently, a specific nutritional combination containing fish oil, specific oligosaccharide mixture, high protein content and leucine has been developed aimed to support the immune system of cancer patients in order to reduce the frequency and severity of (infectious) complications. In a recently modified animal model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 44 publications
(36 reference statements)
5
50
0
Order By: Relevance
“…Whole-blood stimulations were performed with blood samples as previously described (24). Briefly, blood samples taken by cardiac puncture were stimulated with 10 mg/mL OVA in RPMI-1640 (Lonza, Basel, Switzerland) as a final concentration, or the wells were coated with 50 mg/mL anti-CD3 antibody (eBioscience, San Diego, CA, USA) in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Whole-blood stimulations were performed with blood samples as previously described (24). Briefly, blood samples taken by cardiac puncture were stimulated with 10 mg/mL OVA in RPMI-1640 (Lonza, Basel, Switzerland) as a final concentration, or the wells were coated with 50 mg/mL anti-CD3 antibody (eBioscience, San Diego, CA, USA) in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…This medical food is high in protein and leucine and is enriched with emulsified fish oil (containing eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)) and a specific oligosaccharide mixture and is designed to reduce complications and to provide optimal treatment support by reducing the inflammatory state, supporting immune function and nutritional status, and preserving muscle mass and function. These effects have been demonstrated in previous preclinical studies using an animal model of tumor-induced cachexia 21,22. The aim of this exploratory study was to investigate the effects of this medical food on immune function, nutritional status, and inflammation in an early phase in a group of newly diagnosed patients with esophageal cancer or adenocarcinoma of the gastro-esophageal junction before the start of anticancer therapy and to compare this with routine care 1…”
Section: Introductionmentioning
confidence: 95%
“…In this model we observed that a dietary intervention combining fish oil, high protein and leucine had a synergistic effect on the maintenance of body composition (20,21). while the individual components preserved neither fat nor muscle mass, the combination preserved them both.…”
Section: Introductionmentioning
confidence: 76%
“…In a milder c26 model for cachexia without anorexia, the nutritional combination of leucine, high protein, fish oil and specific oligosaccharides (20,21,(51)(52)(53)(54)(55) significantly reduced the loss of carcass, muscle and fat mass. Moreover, this specific combination also improved muscle performance, daily activity and immune function (th1 response) (20,21). these results further strengthen the evidence that a balanced combination of ingredients might achieve multiple effects on the complex conditions of cachexia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation